2007
DOI: 10.1523/jneurosci.3662-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activity Is Modulated by Trial History: A Functional Magnetic Resonance Imaging Study of the Effects of a Previous Antisaccade

Abstract: Saccadic latencies are influenced by what occurred during the previous trial. When the previous trial is an antisaccade, the latencies of both prosaccades and antisaccades are prolonged. The aim of this study was to identify neural correlates of this intertrial effect of antisaccades. Specifically, based on both monkey electrophysiology and human neuroimaging findings, we expected trials preceded by antisaccades to be associated with reduced frontal eye field (FEF) activity relative to those preceded by prosac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 57 publications
9
70
0
Order By: Relevance
“…Indeed, such subjects display longer RTs and worse performance. In humans, procrastination following antisaccade has been associated with neural modulation in the frontal eye field (FEF) and PF measured using magnetoencephalography [19] and functional magnetic resonance imaging [20] approaches.…”
Section: Recent Actions Impact Future Behaviour and Neural Activitymentioning
confidence: 99%
“…Indeed, such subjects display longer RTs and worse performance. In humans, procrastination following antisaccade has been associated with neural modulation in the frontal eye field (FEF) and PF measured using magnetoencephalography [19] and functional magnetic resonance imaging [20] approaches.…”
Section: Recent Actions Impact Future Behaviour and Neural Activitymentioning
confidence: 99%
“…Furthermore, shorter reaction time latencies of the motor response were associated with an increase in the neural activity in the superior colliculus when the previous trial was the same as the current trial (Dorris et al 2000;Fecteau and Munoz 2003;Gore et al 2002). Similarly, fMRI (Manoach et al 2007) and magnetoencephalography (MEG) (Lee at al. 2011) studies of antisaccade-prosaccade tasks in humans have shown changes in the activity of the frontal eye fields to be correlated with previous antisaccade trials and greater reaction time latencies.…”
Section: Neural Bases Of Action Planning In Response To Uncertainty Omentioning
confidence: 99%
“…Therefore the effects could have originated from high cognitive control areas such as SEF and dorsolateral prefrontal cortex (Desouza et al 2003) and propagate to, and take effect in, the eye movement control areas like FEF and SC. The location probability effects are likely to take place in the FEF and the SC by increasing the motor preparation level and consequently decreasing the saccade latencies (Connolly et al 2002(Connolly et al , 2005Koval et al 2004;Manoach et al 2007). …”
Section: General Conclusionmentioning
confidence: 99%